Evaluation Irrigation Institution Aspect in Rice Farming System on Banjarbaru, South Kalimantan - Mustaniroh, Siti Asmaul (Jurnal Teknologi Pertanian, 2001)
This research is designed to evaluated institution aspect of irrigation in rice farming system. Methods of analysis use indicator value  about physical condition (irrigation and drainage facilities), personal, treatment of irrigation system, and organization (P3A, PTGA). The result from analysis that condition in area is not good but enough to increase useful of water in area. For optimize of production  rice farming system, developer of project must control  irrigation system, so can be rehabilitate of irrigation and drainage facilities.Key words : evaluation, institution aspect of irrigation